The gut-brain axis: Impact of social isolation in adolescence. (September 2021) - Lopizzo, Nicola; Marizzoni, Moira; Mazzelli, Monica; Begni, Veronica; Borruso, Luigi Maria; Riva, Marco A; Cattaneo, Annamaria
Abstract : Background: Exposure to early adverse experiences induces persistent changes predisposing the individual to an enhanced vulnerability to develop physical and mental disorders during lifespan. The adverse outcomes depend upon the timing of the stressful experiences, which may differentially influence specific brain regions and biological systems. Methods: In our study we aimed to evaluate, in a preclinical model, changes over time in the microbiome community structure in physiological condition and in response to stress during adolescence. We also aimed to correlate the stressed microbiota composition to the inflammatory status in brain and peripheral blood. Results: Principal coordinate analysis revealed that microbial changes were influenced by age in both isolated and controls rats, regardless of sex, whereas social isolation impacted the microbial composition in a sex-dependent manner. In brain areas we found a specific inflammatory pattern, especially in dorsal hippocampus and prefrontal cortex, significantly correlated with gut microbiota composition. Conclusion: In this study we reported a novel association between long-lasting changes in gut microbiota composition and inflammatory response related to social isolation paradigm during adolescence.